The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ans.16090
|View full text |Cite
|
Sign up to set email alerts
|

Scoping review of head and neck neoplasms presenting with obstructive sleep apnoea: the importance of flexible nasendoscopy

Abstract: Background Obstructive sleep apnoea (OSA) can be caused by neoplasms involving the upper aerodigestive tract. Currently, many of these patients have this diagnosis missed, as most adults diagnosed with OSA do not undergo adequate head and neck examination including flexible nasendoscopy. We performed a review of the literature to shed light on this phenomenon and outline the pathologies and issues surrounding this sub‐population of patients diagnosed with OSA. Methods A scoping review of the literature was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Table 2 OSA due to abscesses formed the bulk of our sample (n = 59,60.82%) [53] followed by HNAL (n = 33,34.02%) [54][55][56][57]. Other unique pathologies mimicking OSA in our series presented as large crops over a short duration.…”
Section: Covid-19 Statusmentioning
confidence: 68%
“…Table 2 OSA due to abscesses formed the bulk of our sample (n = 59,60.82%) [53] followed by HNAL (n = 33,34.02%) [54][55][56][57]. Other unique pathologies mimicking OSA in our series presented as large crops over a short duration.…”
Section: Covid-19 Statusmentioning
confidence: 68%
“…Head and neck cancer should be considered in patients experiencing symptoms besides typical symptoms of OSA and particularly in patients with lower BMI. A scoping review of Moore and colleagues summarized 79 cases of OSA being the leading symptom of head and neck cancer [30]. The authors suggested flexible nasal endoscopy as a potential tool for OSA evaluation in selected individuals since the causative malignant pathology was visible in all examined patients [30].…”
Section: Obstructive Sleep Apnea and Cancer Riskmentioning
confidence: 99%
“…This condition represents a major risk for triggering diseases such as hypertension, ischemic heart disease, diabetes, arrhythmias, or mental illnesses. As a result, it affects the quality of life in a direct way [1].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation methods and local examination, such as nasopharyngoscopy, oropharyngoscopy, and laryngoscopy, allow for the evaluation of the upper airway, the oral cavity, the pharynx, the larynx, the salivary glands, and the thyroid region [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation